Perbandingan Implementasi Model Pembelajaran Inovatif Dalam Meningkatkan Minat dan Keterampilan Berpikir Kritis Siswa Pada Muatan IPA di SD - Marliah M; Ahmad Suriansyah; Wahdah Refia Rafianti (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to compare the effectiveness of the implementation of innovative learning models in improving learning interest and critical thinking skills of elementary school students in science content. The focus of the comparison is the Senter Learning Model (Problem-Based Learning, Student-Centered Learning, Numbered Heads Together) and a combination of Problem-Based Learning, Group Investigation, and Make a Match models. The study was conducted in two elementary schools in Banjarmasin, each of which implemented a different learning model. The research method used classroom action research (CAR) with a quantitative and qualitative approach. Data were obtained through observation, interviews, learning interest questionnaires, and critical thinking skills tests. Data analysis was carried out by comparing the results of each learning cycle. The results showed that both learning models had a positive effect on increasing students' learning interest and critical thinking skills. However, the combination of the Problem-Based Learning, Group Investigation, and Make a Match models proved to be more effective, especially in encouraging active student involvement and problem analysis skills. In contrast, the Senter Learning Model was superior in creating a pleasant learning atmosphere and increasing students' learning motivation.